Compression Behavior of Hybrid Tubes for Lightweight Steel Structures - Gregorio Torres-Escobar (MDPI AG, 2021)
This research shows the results of an experimental investigation carried out on the compression behavior of hybrid steel tubes formed by two concentric steel tubes and four different fillers of non-metallic material interposed between both tubes: polyurethane foam, polyurethane, epoxy and a cement-based mortar. The tests show that the incorporation of a resistant filler in the double tube allows it to improve its mechanical behavior by allowing a second load cycle. Furthermore, the strain energy absorbed during the two cycles led to the conclusion that the epoxy-filled tube absorbed more energy per unit of weight than the other resistant fillers.